2020
DOI: 10.3390/bs10120178
|View full text |Cite
|
Sign up to set email alerts
|

Improving Dignity of Care in Community-Dwelling Elderly Patients with Cognitive Decline and Their Caregivers. The Role of Dignity Therapy

Abstract: Demographic changes have placed age-related mental health disorders at the forefront of public health challenges over the next three decades worldwide. Within the context of cognitive impairment and neurocognitive disorders among elderly people, the fragmentation of the self is associated with existential suffering, loss of meaning and dignity for the patient, as well as with a significant burden for the caregiver. Psychosocial interventions are part of a person-centered approach to cognitive impairment (inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 85 publications
0
7
1
Order By: Relevance
“…However, unlike the results of the previous studies, in the study by Ounalli et al [17] it was found that when a child develops a life-threatening illness, parents use longterm strategies to cope with imminent death. They try to adapt to the shock and hopelessness and, while preparing for the possible death of their child, help their child experience less pain and endure it.…”
Section: Introductioncontrasting
confidence: 58%
“…However, unlike the results of the previous studies, in the study by Ounalli et al [17] it was found that when a child develops a life-threatening illness, parents use longterm strategies to cope with imminent death. They try to adapt to the shock and hopelessness and, while preparing for the possible death of their child, help their child experience less pain and endure it.…”
Section: Introductioncontrasting
confidence: 58%
“…Certainly, some studies done on continuing bonds have shown how these allow an individual to better overcome the suffering of mourning 80 , 81 . Originally, the project planned to develop representations of death by expanding the horizon to include reflection on transcendence to allow minors to think that death does not mean the absolute loss of a loved one, as death education experiences have shown 82 84 .…”
Section: Discussionmentioning
confidence: 99%
“…The practitioner engages in a semistructured interview where a preliminary dignity document is created, which is then edited together with the client, and returned to the client to have and share with family as they see fit. Ounalli et al (2020) stated that dignity therapy is easily modified for those experiencing cognitive impairment, as palliative care should not be considered an intervention for only the dying, but a response to clinical suffering. The intervention can look at the issues of dignity in the context of the losses that those with cognitive impairment may be suffering without parentification or infantilization of the individual.…”
Section: Enhancing Client Dignitymentioning
confidence: 99%